Thoughtful interaction design a design perspective on information technology - Löwgren, Jonas (MIT Press, 2004)
How to think about the shaping and composing of information technology from a design perspective: the aesthetics and ethics of interaction design.
Keywords: System design.; Human-computer interaction.; User interfaces (Computer systems); elektronické knihy; electronic books